Staging postcommunism : alternative theatre in Eastern and Central Europe after 1989 - Warner, Vessela S., 1968-; Manole, Diana, 1963- (Studies in theatre history and culture., 2020)
"After the fall of the Berlin Wall in 1989, East Central European theatre was never the same. In the transition to a post-communist world, 'alternative theatre' found ways to grapple with political chaos, corruption, and aggressive implementation of a market economy. Three decades later, this volume is the first comprehensive examination of alternative theatre in twenty former communist countries. The essays focus on companies and artists that radically changed the language and organization of theatre in the former Eastern European bloc. Essayists view alternative theatre as a cultural, social, and political practice that seized newfound freedom and power after the toppling of censorious totalitarian governments. Emerging from cultural isolation, alternative theatre used experimental, avant-garde performance styles to bring about social and political changes. Ultimately, this collection investigates the ways in which post-communist alternative theatre negotiated and embodied change not only locally but globally as well. The result is a long overdue examination that will be a valuable resource for theatre history, post-Cold War, and Eastern European scholars alike"--